PERMASALAHAN PERKEMBANGAN BAHASA ANAK USIA DINI - Fauziah Nasution; Amanda Siregar; Tria Arini; Vira Ulfia Zhani (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
This study investigates the factors that influence language development in early childhood. This study uses the literature review method to find out what are the factors that influence language development in early childhood. The results showed that genetic factors play a role in the speed and ability of children's language development. A social environment that is rich in language interaction and stimulation has positive impacts, including the quality of conversation, exposure to vocabulary, and opportunities for role playing. Parental education also plays an important role in providing appropriate language stimulation. On the other hand, limited language stimulation and lack of parental support can hinder children's language development. This research highlights the importance of creating an environment that provides adequate language stimulation and involves the active support of parents to support early childhood language development.